COMPARATIVE STUDY BETWEEN CONVENTIONAL PAWNSHOPS AND SHARIA PAWNSHOPS: BENEFITS, CHALLENGES, AND IMPLICATIONS FOR CUSTOMERS - Manihuruk, Frido Evindey; Syahbana, Eza; Alisya, Jeane; Siregar, Filza Azkiah; Marbun, Jonatan; Simbolon, Daniel Sanggam Luhutan; Alnaya, Diva; Rozaini, Noni (Universitas Islam Darul 'ulum Lamongan, 2025)
This research seeks to uncover the advantages and disadvantages between conventional pawnshops and Islamic pawnshops. The focus of the research is on the advantages, challenges, and implications of both types of pawnshops for customers. This research is a descriptive qualitative type with a comparative study technique based on data from previous research. Conventional pawnshops operate based on an interesting system, while Sharia pawnshops use usury-free Sharia principles and prioritize murabahah and ijarah contracts. The results show that conventional pawnshops tend to be more flexible in terms of requirements and processes, but are subject to interest charges that can be burdensome for customers. Islamic pawnshops, on the other hand, offer a fairer solution that complies with Islamic financial principles, although they often face challenges in terms of public understanding and more complex procedures. The implications for customers depend largely on their needs, understanding and values, with choices having to take into account both financial aspects and compliance with sharia principles. This research provides insights for customers in choosing the type of pawnshop that suits their needs and values.